Long Noncoding RNA RP11-380D23.2 Drives Distal-Proximal Patterning of the Lung by Regulating PITX2 Expression. (29th November 2017) - Banerjee, Poulomi; Surendran, Harshini; Bharti, Kapil; Morishita, Kaoru; Varshney, Anurag; Pal, Rajarshi
Abstract : Early lung development is a tightly orchestrated process encompassing (a) formation of definitive endoderm, (b) anteriorization of definitive endoderm, followed by (c) specification and maturation of both proximal and distal lung precursors. Several reports detailing the interaction of genes and proteins during lung development are available; however, studies reporting the role(s) of long noncoding RNAs (lncRNA) in lung morphogenesis are limited. To investigate this, we tailored a protocol for differentiation of human-induced pluripotent stem cells into distal and proximal lung progenitors to mimic in vivo lung development. The authenticity of differentiated cells was confirmed by expression of key lung markers such as FoxA2, Sox-17, Nkx2.1, Pitx2, FoxJ1, CC10, SPC, and via scanning as well as transmission electron microscopy. We employed next generation sequencing to identify lncRNAs and categorized them based on their proximity to genes essential for lung morphogenesis. In-depth bioinformatical analysis of the sequencing data enabled identification of a novel lncRNA, RP11-380D23.2, which is located upstream of PITX2 and includes a binding site for PARP1. Chromatin immunoprecipitation and other relevant studies revealed that PARP1 is a repressor for PITX2. Whole genome microarray analysis of RP11-380D23.2/PITX2 knockdown populations of progenitors demonstrated enrichment in proximal progenitors and indicated altered distal-proximal patterning. Dysregulation of WNT effectors in both knockdowns highlighted direct modulation of PITX2 by RP11-380D23.2. Most of these results were validated in four independent hiPSC lines (including a patient-specific CFTR mutant line). Taken together, these findings offer a mechanistic explanation underpinning the role of RP11-380D23.2 during lung morphogenesis via WNT signaling. Abstract : Long non-coding RNA RP11-380D23.2 modulates its nearest protein-coding gene PITX2 thereby allowing its interaction with CTNNB1 resulting in the maintenance of left–right symmetry during lung development. Binding of PARP1 represses PITX2 triggering inactivation of the WNT axis leading to impairment of distal proximal lung patterning.